Assessment of phosphorus removal performance of subsurface constructed wetland during dry and wet conditions - Fai C.M.; Haris H.; Chin S.Z. (American Institute of Physics Inc., 2023)
This study is aimed to determine the removal efficiencies of phosphorus in subsurface constructed wetland under wet and dry conditions. A total of six storm events which comprise of dry and wet conditions were monitored for stormwater samples collection at the inlet and outlet of studied wetland. All samples are analyzed for its orthophosphate (PO4) and total phosphorus (TP) concentrations. The event mean concentration (EMC) is determined for each pollutant in every storm event in order to quantify the stormwater quality. The efficiency ratio is calculated for determining the removal efficiency of phosphorus by the constructed wetland. The results indicated that the removal efficiencies of PO4 is reducing during the continuous storm events (wet condition) while increasing during the intermediate drying condition. The mean PO4 and TP removal efficiencies for wet condition are 63.7% and 57%, while 76% and 74.5% for dry condition, respectively. The findings show that intermediate drying effect will improve the removal efficiencies of phosphorus in subsurface constructed wetland. 2021 American Institute of Physics Inc.. All rights reserved.